Customer satisfaction with iPay Mobile services at VietinBank -Hanoi branch - Dang, Thanh Van (H. : ĐHQGHN, 2020)
The thesis has found that all six factors: Tangible - Perceived ease to use - Safety and Security - speed and Service capabilities - Responsiveness - Service charge have impact on customer satisfaction with iPay Mobile services at VietinBank - Hanoi branch. In particular, responsiveness is the factor that has the strongest impact on customer satisfaction.